The impacts of land-use changes on the recovery of saltmarshes in Portugal - Almeida, Diana (2014)
Human-induced land-use changes have resulted in loss and degradation of intertidal environments worldwide. Saltmarsh ecosystem dynamics in Portugal are greatly influenced by historic uses and consequent habitat degradation. This study uses an original approach combining vegetation surveys and spatial analysis of historic maps and aerial photographs to assess the effects of land use changes on saltmarshes in two areas in the Algarve, southern Portugal. Historical maps from c. 1800 and aerial photographs from 1958 to 2010 were analyzed to map saltmarsh ecosystems and quantify land-use changes in the Alvor estuary and Arade River. Between c. 1800 and 2010 more than half of saltmarshes were lost due to dyke building and saltmarsh reclamation for agriculture. In mid-1960s, the abandonment of reclaimed agricultural areas resulted in the recolonization of saltmarsh vegetation, which developed physically separated from natural marshes. In the study area, these saltmarshes naturally evolved into two distinct typologies: (1) enclosed mixed marshes, formed by patches of brackish, freshwater and some invasive species developing due to saline intrusion in areas where dykes have not been breached; and (2) tidally-restored saltmarshes, formed in areas where dyke breaching allows incursion of tides and development of a vegetation structure similar to natural saltmarshes. In Europe, passive (without human intervention) and active (artificially planned) saltmarsh restoration are important mechanisms for voluntary or statutory re-creation of intertidal habitats. Improved understanding of the factors influencing the development of distinct saltmarsh typologies through passive ecosystem recovery can provide new insights to support decision-making concerning intertidal habitat restoration.